Comparison of the Effects of Mesenchymal Stem Cells with Their Extracellular Vesicles on the Treatment of Kidney Damage Induced by Chronic Renal Artery Stenosis - Crysthiane Saveriano Rubiao Andre Ishiy; Milene Subtil Ormanji; Edgar Maquigussa; Rosemara Silva Ribeiro; Antonio da Silva Novaes; Mirian Aparecida Boim (Stem Cells International)
Background. Chronic renal artery stenosis is considered one of the most common causes of renovascular hypertension (RH). Chronic hypoxia can lead to irreversible damage to renal tissue and to a progressive deterioration of renal function. We have previously shown that bone marrow-derived mesenchymal stem cells (BMSCs) improved renal parenchyma and function in a model of RH (2 kidneys, 1 clip model (2K-1C) in rats. Microvesicles (MVs) and exosomes (EXs) released by MSCs have been shown to induce effects similar to those induced by whole cells but with fewer side effects. In this study, we compared the effects of adipose-derived MSCs (ASCs) with those of the MVs and EXs released by ASCs on tissue inflammation and renal function in 2 K-1C rats. Results. Flow cytometry analysis showed that even after 15 days, ASCs were still detected in both kidneys. The expression of a stem cell homing marker (SDF1-α) was increased in ASC-treated animals in both the stenotic and contralateral kidneys. Interestingly, SDF1-α expression was also increased in MV- and EX-treated animals. A hypoxia marker (HIF1-α) was upregulated in the stenotic kidney, and treatments with ASCs, MVs, and EXs were effective in reducing the expression of this marker. Stenotic animals showed a progressive increase in systolic blood pressure (SBP), while animals treated with ASCs, MVs, and EXs showed a stabilization of SBP, and this stabilization was similar among the different treatments. Stenotic animals developed significant proteinuria, which was reduced by ASCs and MVs but not by EXs. The increased expression of Col I and TGFβ in both kidneys was reduced by all the treatments, and these treatments also effectively increased the expression of the anti-inflammatory cytokine IL-10 in both kidneys; however, only ASCs were able to reduce the overexpression of the proinflammatory cytokine IL-1β in both kidneys of 2K-1C animals. Conclusion. The results of this study demonstrated that the EVs released by ASCs produced beneficial results but with lower efficacy than whole cells. ASCs produced stronger effects in this model of renal chronic hypoxia, and the use of EVs instead of whole cells should be evaluated depending on the parameter to be corrected.